THE ROLE OF HALAL LABELIZATION AND BRAND IMAGE IN OPTIMIZATION OF SALES AT HISANA FRIED CHICKEN BRANCH ALFALAH RAYA MEDAN EAST - Aurel, Vira; Mariska, Septiara Dwi; Harahap, Fikri Rizalsyah; Hayati, Isra (Proceeding International Seminar of Islamic Studies, 2024)
Abstract: This research aims to determine the role of halal labeling and brand image in optimizing sales of Hisana fried chicken at the Alfalah Raya branch in East Medan. The research approach used is a qualitative approach and the data sources used are data sources through observation and interviews. The data analysis technique used is descriptive data analysis. In this research, the interviewee was the owner of Hisana Fried Chicken. The research results show that the role of halal labeling and brand image is quite important in optimizing sales. Halal labeling aims to increase consumer confidence and expand the market for halal products. The role of a unique and recognizable brand image can increase brand visibility, attract customers and differentiate it from other products, which ultimately leads to increased sales.Keywords: (halal labeling, brand image and sales optimizaton)